Current Status and Changes in Pain and Activities of Daily Living in Elderly Patients with Osteoarthritis Before and After Unilateral Total Knee Replacement Surgery - Lai, Yen-Feng; Lin, Pei-Chao; Chen, Chung-Hwan; Chen, Jyu-Lin; Hsu, Hsin-Tien (Journal of clinical medicine, 2019)
Knee osteoarthritis (OA) is a very common disease in the elderly, and total knee replacement (TKR) surgery is currently considered the most effective treatment. A prospective, observational, repeated measures study was performed to explore the current status and changes in pain and activities of daily living (ADL) in 58 OA elderly patients undergoing unilateral TKR. The Wong–Baker Faces Pain Rating Scale (WBS) for pain and the self-reported Barthel Index for ADL were measured on the day before surgery, 48 hours after surgery, and the day before discharge. Moderate pain was reported before surgery. Pain significantly improved after surgery and before discharge. At all three time points, pain scores were significantly higher in patients who used assistive devices compared to those who did not. Partial independence in ADL was reported before surgery. The ADL scores reported were highest before surgery, and those reported after surgery were lowest. However, ADL scores gradually increased before discharge. ADL scores were higher in the subjects who lived in a detached, single-family homes compared to those who lived in bungalows at all three time points. The results could be used to screen for knee OA elderly patients at high-risk for pain or low ADL and to provide timely intervention strategies as soon as possible.